Assessing Risk Aversion From the Investor’s Point of View - Díaz, Antonio; Esparcia, Carlos (Frontiers in Psychology, 2019)
Throughout the financial literature, there is a great deal of debate about the nature of investors' risk preferences. In an ever-changing world, the main schools of knowledge discuss the constant or dynamic basis of these preferences. Based on an exhaustive review of the subject of risk aversion, this paper contributes to filling the gap that exists in the literature on the risk aversion parameter that best fits the investors’ behavior towards risk. The main determinants of risk attitude are examined and the different and most novel methodologies and perspectives are carefully analyzed.